Composite diffuse large B-cell lymphoma and peripheral T-cell lymphoma: a case report with two-year follow-up and literature review - Gu, Jiwei; Qian, Juan; Cao, Xin (Frontiers in Oncology, 2024)
Composite lymphoma is an uncommon type of lymphoid malignancy, and those consisting of concurrent diffuse large B-cell lymphoma (DLBCL) and peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS) in the same organ are rare. Here, we report a case of a 75-year-old male patient admitted to our emergency department with intestinal obstruction presenting with abdominal pain and vomiting. He underwent partial resection of the small intestine under general anesthesia, and subsequent histopathology confirmed the mass to be composite DLBCL and PTCL-NOS. The patient received chemotherapy with a rituximab-based regimen and achieved complete remission (CR).However, the recurrent disease presented with obstruction again ten months after treatment. He refused a second surgery, but salvage treatment was not effective. The patient survived for 20 months after diagnosis. In addition, we did a literature review to understand the clinical features, pathology, treatment, and prognosis of this type of composite lymphoma.